2021
DOI: 10.2147/jir.s307884
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circulating Biomarkers and Construction of a Prognostic Signature for Survival Prediction in Locally Advanced Pancreatic Cancer After Irreversible Electroporation

Abstract: Background Irreversible electroporation (IRE) is a novel treatment for locally advanced pancreatic cancer (LAPC), but the predictive factors, based on cytokines and immunocytes of survival, are still lacking. This study aimed to establish a risk model based on cytokines and immunocytes for LAPC patients undergoing IRE treatment. Patients and Methods Peripheral blood samples were obtained from 31 LAPC patients and 8 healthy control subjects before IRE. The phenotypes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Thus, apart from inducing apoptosis of tumor cells, IRE can also reconstruct the microenvironment within the tumor and induce the immune response. [9][10][11] Previous studies had shown that IRE could alleviate immune suppression and induce activation of T cells, indicating that IRE may potentiate the antitumor efficacy of immunotherapy in PDAC. 9,12 In recent years, game-changing advances have been achieved in the development of therapies of various cancers, including melanoma, lung and liver cancers with immune checkpoint inhibitors (ICIs).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, apart from inducing apoptosis of tumor cells, IRE can also reconstruct the microenvironment within the tumor and induce the immune response. [9][10][11] Previous studies had shown that IRE could alleviate immune suppression and induce activation of T cells, indicating that IRE may potentiate the antitumor efficacy of immunotherapy in PDAC. 9,12 In recent years, game-changing advances have been achieved in the development of therapies of various cancers, including melanoma, lung and liver cancers with immune checkpoint inhibitors (ICIs).…”
Section: Introductionmentioning
confidence: 99%